PENGELOLAAN LINEN OLEH LAUNDRY SECTION DI HOTEL GRAND JATRA KOTA PEKANBARU - Shinta Pradina; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Laundry Department is one of the departments in the hotel that is responsible for washing, both washing guest clothes (laundry, dry cleaning and pressing), employee uniforms and hotel linens (house laundry) and washing clothes or linen from outside the hotel (outside laundry). Therefore, every hotel should improve linen management by the laundry section. This study aims to determine how the management of linen by the laundry section, the constraints and efforts made at the Grand Jatra Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. The data collection techniques used were observation, documentation, and interviews with laundry managers, laundry supervisors and laundry employees at Grand Jatra Hotel Pekanbaru. After conducting interviews with informants, the authors concluded that the management of linen by the laundry section was good enough, because the laundry staff had implemented it in accordance with the directions set by the laundry manager. Keywords: Management, Linen, Laundry Section